Developing and measuring healthcare capacity and quality in Burundi: LifeNet International's horizontal conversion franchise model - Michael F Brooks; Maggie Ehrenfried (Health for All Nations, 2016)
In a departure from traditional "vertical" healthcare interventions in low-resource settings that work to combat a single specific health issue, LifeNet International (LN) uses a horizontal conversion franchise to develop and measure healthcare capacity and quality in primarily faith-based health centers in East Africa. Through a comprehensive franchise package of Medical Training, Management Training, Pharmaceutical Supply, and Growth Financing, LN is able to leverage existing resources and respond to a greater number of the obstacles preventing facilities from providing quality care. Through its Quality Score Card, LN measures improvements in quality of care within its network. This tool has measured consistent and significant improvements in quality of care following LN partnership. Together, these services improve quality of care at East African primary care facilities in ways that issue-specific, "vertical" interventions cannot.